Design Dilemma: Driving a Consumption Obsessed Society into an Unsustainable Future - Smith, Nicola Dawn (QUT, Brisbane, 2011)
It is well known that as Australians we have, by global standards, a high standard of living but a wholly unsustainable way of life. There is an urgent need to rationalise the way we establish our home environment and modify it to our specifications, and an equally important need to investigate the way in which design influences the ambitions and aspirations driving the consumption around home-making. This paper reports on early investigation into everyday design influences on our unsustainable lifestyles with a focus on the domestic housing market, and the process of home-making and re-making. Shelter, security and comfort are fundamental premises of making home, and yet many people have ambitions far beyond the basic requirements when they search for the perfect home environment. Contributions from participants in the author's doctoral study will provide personal reflections on the dilemmas faced by people trying to match their homes with their aspirations and creativity. It will be seen that the real estate, design and media industries should bear some responsibility for fuelling consumption based behaviour and contribute to reshaping the current desire for a dream home. Re-focusing lifestyle aspirations will also require increasing awareness about the social, environmental and economic benefits of developing creative and craft-based skills through home-focused sustainability practices.